Emerging Strategies of Cancer Therapy Based on Ferroptosis. Issue 12 (22nd January 2018) - Shen, Zheyu; Song, Jibin; Yung, Bryant C.; Zhou, Zijian; Wu, Aiguo; Chen, Xiaoyuan
Abstract: Ferroptosis, a new form of regulated cell death that is iron‐ and reactive oxygen species dependent, has attracted much attention in the research communities of biochemistry, oncology, and especially material sciences. Since the first demonstration in 2012, a series of strategies have been developed to induce ferroptosis of cancer cells, including the use of nanomaterials, clinical drugs, experimental compounds, and genes. A plethora of research work has outlined the blueprint of ferroptosis as a new option for cancer therapy. However, the published ferroptosis‐related reviews have mainly focused on the mechanisms and pathways of ferroptosis, which motivated this contribution to bridge the gap between biological significance and material design. Therefore, it is timely to summarize the previous efforts on the emerging strategies for inducing ferroptosis and shed light on future directions for using such a tool to fight against cancer. Here, the current strategies of cancer therapy based on ferroptosis will be elaborated, the design considerations and the advantages and limitations are highlighted, and finally a future perspective on this emerging field is given. Abstract : Iron‐ and indirect iron‐based nanomaterials can be developed for ferroptosis‐based cancer therapy via release of their own iron or loaded endogenous iron in lysosomes after endocytosis, which can employ the Fenton reaction to produce reactive oxygen species and induce lipid peroxidation. Such systems are reviewed for application in cancer therapy.